Building Resilience Against Populism: The Crucial Role of Education in Promoting Human Dignity - Kleindienst Petra (Politics in Central Europe)
In an era marked by the rise of populist movements, this article examines the role of education in reducing the effects of this phenomenon, particularly their often-detrimental impact on the concept of human dignity. The study investigates the ways incorporating ‘education on human dignity’ in the curricular activities can help counterbalance the divisive and sometimes dehumanising rhetoric of populism. The findings of the article point to the importance of education as a transformative force for making young minds able to critically assess and challenge the divisive narratives found in today’s political landscape. In that context, the article discusses educational policies that could assist in fostering the realisation of human dignity in countries encountering the rise of populist ideologies. Finally, the article provides valuable insights and practical recommendations for educators and policymakers with the aim of ensuring that human dignity is viewed more holistically in education.